Closed Circuit Television CCTV Installation, Maintenance and Operation. - Cieszynski, Joe. (Burlington : Elsevier, 2003)
Closed Circuit Television (CCTV) surveillance is one of the important areas in the security industry. This book provides information for professionals involved in the installation and maintenance of CCTV systems, system design, specification and purchasing and the management of CCTV systems.
Contents; Preface; Acknowledgements; 1 The CCTV industry; 2 Signal transmission; 3 Light and lighting; 4 Lenses; 5 Fundamentals of television; 6 The CCTV camera; 7 Monitors; 8 Recording equipment; 9 Camera switching and multiplexing; 10 Telemetry control; 11 Ancillary equipment; 12 Commissioning and maintenance; Glossary of CCTV terms; Index.
Keywords: Closed-circuit television; Television; Electronic books